Systematic Review and Meta-Analysis of Randomized Controlled Trials of Liangxue Tongyu Formula on Patients With Acute Intracerebral Hemorrhage - Jiang, Chao; Yang, Xiaojuan; Dong, Ju; Li, Guochun (Frontiers in Pharmacology, 2020)
Background: As a traditional Chinese medicine prescription for acute stroke, Liangxue Tongyu formula (LXTYF) was widely used as auxiliary treatment measure in some clinical practice. This study aimed to evaluate the clinical efficacy and safety of LXTYF combined western conventional medicine (WCM) with WCM only for acute intracerebral hemorrhage (ICH). Methods: We systematically searched PubMed, Embase, Cochrane Library, CMB (Chinese biomedicine database), CNKI (China National Knowledge Infrastructure), WanFang and VIP until August 2019 to confirm relevant randomized controlled trials (RCTs) compared the combination of LXTYF and WCM with WCM alone for the treatment of acute ICH. Two investigators independently assessed the risk of bias, and extracted and analyzed the data from the identified studies using RevMan 5.3.0 software following Cochrane’s standard and PRISMA guidelines. The herbal compositions of LXTYF were also assessed. Results: 15 RCTs were identified, totally recruiting 1648 patients with acute intracerebral hemorrhage. Compared with the WCM alone, the combination therapy of LXTYF with WCM could improve the clinical effective rate (RR=1.21, 95%CI: 1.15 to 1.25, P<0.05) and ADL score (MD=18.09, 95%CI: 12.11 to 24.07, P<0.05), and reduce syndrome scores of the traditional Chinese medicine(TCM) (MD=-4.11, 95%CI: -4.69 to -3.53, P<0.05) and the Glasgow outcome score(GOS) (MD=0.43, 95%CI: 0.06 to 0.79, P=0.02) Moreover, there was no sufficient evidence to indicate the adverse effects would increase compared with WCM alone. Conclusion: Based on current evidence, we concluded that the combined therapy had some benefits in treating acute intracerebral hemorrhage. However, considering the potential biases and limitations of our study, additional large, high-quality RCTs are required in the future to confirm or refute the effects of LFTYF combined with WCM in acute stroke.